The role of different medium and plant hormones on multiple shoots of Jewel orchids (Anoectochilus setaceus Blume) - Thanh, Nguyen Trung; Hang, Pham Luong; Ket, Nguyen Van; Anh, Truong Thi Lan; Phe, Phung Van; Gam, Nguyen Thi Hong; Mien, Phi Thi Cam (VNU Journal of Science: Natural Sciences and Technology; Vol 28 No 1, 2012)
Abstract. Use of Anoectochilus setaceus species have increased in the past few years due to the antidepressant and antiviral activities found in extracts of those plants. As a result of its potential as a pharmaceutical, a new system was developed for in vitro culture of this species. The goal of this investigation was to produce multiple shoot via in vitro techniques for Anoectochilus setaceus . The basal MS and Knud medium were tested and shown to be equally suitable of them for shoot culture of A. setaceus . Othe cultures were initiated from shoots inoculated onto MS medium supplemented individually with six different concentrations of 6-Benzylaminopurine (BAP) and Kinetin (Kn). The highest number of shoots was obtained on medium supplemented with 0.6 mg l -1 BAP (3.8 shoot/explant). Out of all the investigated concentrations of Kn, the best result was obtained on medium supplemented with 1.0 mg l -1 Kn (3.2 shoot/explant). Keywords : Jewel orchids ( Anoectochilus setaceus ), plant hormones, the multiple shoot induction.